A Formal Modeling Framework for the Implementation of Gaze Guiding as an Adaptive Computer-Based Job Aid for the Control of Complex Technical Systems. Issue 8 (8th May 2020) - Weyers, Benjamin; Frank, Barbara; Kluge, Annette
ABSTRACT: This paper presents a comprehensive formal engineering approach for the development of gaze guiding as an adaptive computer-based job aid to support semi-automated technical control tasks. Major requirement for this engineering method was to present a model-based approach, which on the one hand offers a coherent integration of various heterogeneous descriptions of the system, the standard operating procedures to be applied, and the used gaze guiding, and an algorithmic transformation into an executable form on the other. The latter is used as part of a runtime system or execution framework that integrates gaze guiding into an existing graphical user interface as an overlay. To demonstrate the suitability of the resulting model that enables gaze guiding, we present a use case for the modeling approach and we conducted a user study with 140 participants who worked on three different types of SOPs. The study showed the positive impact of the gaze guiding and its potential to suite as an adaptive computer-based job aid. The results confirmed findings from previous studies and showed decreased numbers of errors during the execution of the start-up procedure if gaze guiding was used.